2018
DOI: 10.1029/2018gl078127
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Atmospheric Methane From Fossil Fuel and Microbial Sources Over the Last Three Decades

Abstract: Atmospheric measurements show an increase in CH 4 from the 1980s to 1998 followed by a period of near-zero growth until 2007. However, from 2007, CH 4 has increased again. Understanding the variability in CH 4 is critical for climate prediction and climate change mitigation. We examine the role of CH 4 sources and the dominant CH 4 sink, oxidation by the hydroxyl radical (OH), in atmospheric CH 4 variability over the past three decades using observations of CH 4 , C 2 H 6 , and δ 13 C CH4 in an inversion. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(130 citation statements)
references
References 70 publications
7
120
2
1
Order By: Relevance
“…A parallel contributory hypothesis is that a decline in biomass burning emissions has masked a strong increase in fossil fuel emissions, given evidence suggesting reduced burning in the 2001-2014 period (Worden et al, 2017). As noted above, Thompson et al (2018) also infer that fossil fuel sources increased in 2006-2014, while biomass burning decreased. Methane from fires, especially in tropical savannas dominated by C4 grasses, is much enriched in δ 13 C CH4 Dlugokencky et al, 2011); thus, pulses of methane from tropical savanna and peatland fires (δ 13 C CH4 around −30‰ to −15‰) have strong leverage on ambient values.…”
Section: Has Either a Shift In Fossil Fuel δ 13 C Ch4 Or A Decline Inmentioning
confidence: 97%
See 1 more Smart Citation
“…A parallel contributory hypothesis is that a decline in biomass burning emissions has masked a strong increase in fossil fuel emissions, given evidence suggesting reduced burning in the 2001-2014 period (Worden et al, 2017). As noted above, Thompson et al (2018) also infer that fossil fuel sources increased in 2006-2014, while biomass burning decreased. Methane from fires, especially in tropical savannas dominated by C4 grasses, is much enriched in δ 13 C CH4 Dlugokencky et al, 2011); thus, pulses of methane from tropical savanna and peatland fires (δ 13 C CH4 around −30‰ to −15‰) have strong leverage on ambient values.…”
Section: Has Either a Shift In Fossil Fuel δ 13 C Ch4 Or A Decline Inmentioning
confidence: 97%
“…In this context, Thompson et al () found that OH appears not to have contributed significantly to recent methane growth. Further insight into the OH problem came from Nicely et al () who showed that atmospheric OH is probably currently well buffered, with mean anomalies of 1.6%.…”
Section: Testing the Hypotheses That May Explain The Recent Rise In Mmentioning
confidence: 99%
“…These hypotheses include increased fossil fuel emissions, increased microbial emissions, or some combination of the two allied with other factors (e.g. Schaefer et al, 2016;Hausmann et al, 2016;Worden et al, 2017;McNorton et al, 2018;Thompson et al, 2018). Additionally, we 10 cannot discount a role for a changing OH sink based on CH 4 , isotopic δ 13 CH 4 and methyl chloroform observations Turner et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…This constraint is implicitly used in two-box model studies (Rigby et al, 2017;Sapart et al, 2012., Turner et al, 2017 and multiple-box model studies (Nisbet et al, 2016;Thompson et al, 2018). The inter-hemispheric difference (IHD) in CH 4 abundance has been used to quantify the ratio between Northern and Southern Hemisphere CH 4 emissions or sinks.…”
Section: Citationmentioning
confidence: 99%
“…The inter-hemispheric difference (IHD) in CH 4 abundance has been used to quantify the ratio between Northern and Southern Hemisphere CH 4 emissions or sinks. This constraint is implicitly used in two-box model studies (Rigby et al, 2017;Sapart et al, 2012., Turner et al, 2017 and multiple-box model studies (Nisbet et al, 2016;Thompson et al, 2018). Dlugokencky et al (2003) furthermore introduced the metric inter-polar difference (IPD) as the difference between the annual averages of CH 4 from northern (53°N to 90°N) and southern (53°S to 90°S) polar regions, weighted with the inverse sine of latitude.…”
Section: 1029/2018gl081092mentioning
confidence: 99%